CARBAPENEMASES AND GRAM-NEGATIVE BACTERIA: A REVIEW - Ramalingam, Aishwarya J (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The emergence of resistance in Gram-negative pathogens has alarmed many clinicians and health-care workers both in community and hospital settings. Antibiotics, such as carbapenems, are used as a last resort in the treatment of multi-drug resistant (MDR) Gram-negative pathogens. Carbapenemases are the enzymes that hydrolyze carbapenems. The global spread of these MDR organisms has posed a public health problem due to its difficulty in empirical treatment of hospital and community acquired infections. Keywords: Carbapenems, Carbapenemase, Gram-negative bacteria, Multi-drug resistant organisms.